Evaluating the Knowledge for Integrating RM and VM Using BIM in the Iraqi Construction Sector (Journal of Engineering, 2024)
The construction industry plays a crucial role in the countries' economy, especially in the developed country. This point encourages the concerned institution to use new techniques and integrate many techniques and methods to maximize the benefits. The main objective of this research is to evaluate the use of risk management, value management, and building information modeling in the Iraqi construction industry. The evaluation process aims at two objectives. The direct objective was to evaluate the knowledge in risk management (RM), value management (VM), and building information modeling (BIM). The indirect objective was to support the participants with information related to the main items mentioned. The questionnaire survey was used as a data collection method. The participants in the survey were engineers from the Iraqi construction sector. The sample size was 121 engineers from 34 institutions with multidisciplinary backgrounds. The results showed that the engineers need to develop the training system and merge many methods and techniques in their institution to maximize the benefits using an integration model capable of dealing with the variable environment in construction, especially in developing countries like Iraq.